2021
DOI: 10.1007/jhep04(2021)086
|View full text |Cite
|
Sign up to set email alerts
|

Two-meson form factors in unitarized chiral perturbation theory

Abstract: We present a comprehensive analysis of form factors for two light pseudoscalar mesons induced by scalar, vector, and tensor quark operators. The theoretical framework is based on a combination of unitarized chiral perturbation theory and dispersion relations. The low-energy constants in chiral perturbation theory are fixed by a global fit to the available data of the two-meson scattering phase shifts. Each form factor derived from unitarized chiral perturbation theory is improved by iteratively applying a disp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 123 publications
(228 reference statements)
0
13
1
Order By: Relevance
“…In principle the photon can also couple to K 0 due to its non-zero charge radius, so F K 0 em (q 2 ) = 0 when q 2 = 0. However, a simple ChPT calculation at O(p 4 ) indicates that |F K 0 em (q 2 )| < 0.02 when |q 2 | < 0.1 GeV 2 (see, e.g., ref [59]…”
mentioning
confidence: 99%
“…In principle the photon can also couple to K 0 due to its non-zero charge radius, so F K 0 em (q 2 ) = 0 when q 2 = 0. However, a simple ChPT calculation at O(p 4 ) indicates that |F K 0 em (q 2 )| < 0.02 when |q 2 | < 0.1 GeV 2 (see, e.g., ref [59]…”
mentioning
confidence: 99%
“…This scalar matrix element itself has been obtained in Ref. [45]. However, its exact NR component is still unknown.…”
Section: B Exptmentioning
confidence: 90%
“…of the correlation function is proportional to the discontinuity in terms of the invariants p 2 V and p 2 π , and the discontinuity only comes from the denominators of the integrand in Eq. (49). It is found that p 2 V and p 2 π do not appear in the same denominator, so we can extract the two imaginary parts independently.…”
Section: Quark-gluon Level Calculation In Lcsrmentioning
confidence: 96%